Enhanced Photovoltaic Performance of Perovskite Solar Cells Based on Er-Yb Co-doped TiO2 Nanorod Arrays. (10th August 2017) - Wang, Xiaoli; Zhang, Zhenlong; Qin, Jianqiang; Shi, Wenjia; Liu, Yuefeng; Gao, Huiping; Mao, Yanli
Abstract: In the present study, Er and Yb co-doped TiO2 (Er-Yb:TiO2 ) nanorod arrays were grown with a hydrothermal method, and perovskite solar cells were fabricated using them as an electron transfer material. The photovoltaic performance of the solar cells based on Er-Yb:TiO2 was enhanced compared with that of solar cells based on un-doped TiO2 . The power conversion efficiency of the solar cells on Er-Yb:TiO2 increased to 13.4%, which is 20.8% higher than that of the solar cells based on un-doped TiO2 . The experimental results indicate that the larger open circuit voltage could be due to the larger conduction band difference between Er-Yb:TiO2 and perovskite material. The enlarged short circuit current could be attributed to the faster electron transfer, reduced recombination, and the upconversion of Er-Yb:TiO2 NRs.